Los tercios en el mar - Pi Corrales, Magdalena de Pazzis (Cuadernos de Historia Moderna, 2006)
This paper looks at the way of the life of the tercios (crack infantry troops of the King of Spain) serving on board navy warships both in the Mediterranean and the stormy waters of the Atlantic Ocean in the first centuries of the Modern Era. This was a time of famous sea battles as Spain strove constantly to maintain its maritime supremacy, and the contribution of the tercios is therefore particularly interesting in this context. Many aspects are analysed, starting with the moment in which troops were first sought to man warships forming part of a naval expedition; other aspects looked at are the selection procedure used, enlistment, the payment, arrival at the embarkation ports and the main recruitment difficulties. An account is also given of the frequent trials and tribulations they suffered in serving long spells aboard these veritable floating fortresses, the wrench of living so far from their normal daily life and families, the difficult sanitary conditions and poor food, the occasional friction and strife with the rest of the crew they had to share space and time with while girding their loins for the combat.....